A Comparative Evaluation of Physical and Chemical Properties of Biodiesel Synthesized from Edible and Non-Edible Oils and Study on the Effect of Biodiesel Blending - Atabani, A. E.; Mahlia, T. M. I.; Masjuki, H. H.; Irfan Anjum, Badruddin; Wan Mohd Hafizuddin, Wan Yussof; Chong, W. T.; Teong Lee, Keat (Elsevier, 2013)
Traditionally, biodiesel has been produced from edible oils due to their low free fatty acids. However, their use has elevated some issues such as food versus fuel and many other problems that have negatively affected their economic viability. Therefore, exploration of non-edible oils may significantly reduce the cost of biodiesel especially in poor countries which can barely afford the high cost of edible oils. This paper aims to produce biodiesel from several edible and non-edible oils that are readily available in the South East Asian market. These oils include; Jatropha curcas, Calophyllum inophyllum, Sterculia foetida, Moringa oleifera, Croton megalocarpus, Patchouli, Elaeis guineensis (palm), Cocos nucifera (coconut), Brassica napus (canola) and Glycine Max (soybean) oils. This was followed by an investigation of physico-chemical properties of the produced biodiesel. This paper also discusses the concept of biodiesel blending to improve some of the properties of these feedstocks. For instance, blending of SFME and CoME improves the viscosity of SFME from 6.3717 mm2/s to 5.3349 mm2/s (3:1), 4.4912 mm2/s (1:1) and 3.879 mm2/s (1:3). The properties of other biodiesel blends were estimated using the polynomial curve fitting method.